Infection and Thrombotic Complications in Peripherally Inserted Central Catheters (PICCs) in Cancer Patients at Healthcare Global Hospital, Bangalore - Sapkota, Sulav; Priyadarshini, Mona; Naik, Radheshyam (Birat Journal of Health Sciences, 2020)
Introduction: Peripherally inserted central catheter (PICC) is a form of vascular access device (VAD) that can be used for a prolonged period of time in cancer patients for diverse indications. Despite the many advantages, catheter related complications are common. Objectives: The objective of this study was to evaluate infection and thrombotic complications of PICCs in cancer patients. Methodology: We conducted a prospective longitudinal study, over a duration of thirty months from June 2015 to December 2017 in the Department of Haematology and Medical Oncology at our tertiary care, cancer hospital to assess, analyze and compare the infection and thrombotic complications in cancer patients with a PICC line. All patients with cancer who met the inclusion criteria were enrolled and were followed up until catheter removal. The basic information regarding PICCs insertion, weekly care and removal was maintained. The data were analyzed and compared to identify catheter related complications Result: Four hundred and sixty-one PICCs were monitored for a total of 57,438 catheter-days (mean of 124 days i.e. 4.15 months, range : 1 to 434 days). Out of these 461 PICCs, 29 (6.29%) had both infection and thrombotic complications, as a result of which 22 were removed in 57,438 catheter days. (ie catheter removal rate was 0.38 per 1000 PICC days). Infection complications were found more with hematological malignancies while thrombotic complication were predominant in solid tumours. Conclusion: Infection complications were more common in hematological cancer patients than solid cancers where thrombotic complications were more common.